Medical Management of Functioning Pituitary Adenoma: An Update - OKI, Yutaka (Neurol Med Chir (Tokyo), 2014)
The treatment of functioning pituitary adenoma (FPA) must achieve endocrinological remission as well as tumor size reduction. The first-line treatment of FPA except prolactinoma is transsphenoidal surgery (TSS). Medical treatments and/or radiation will be applied as adjuvant therapies succeeding to TSS. In patients with prolactinoma, dopamine agonists, especially cabergoline, are quite efficient. Dopamine agonists decrease plasma prolactin levels and induce shrinkage in most patients and can be ceased in some of them. In patients with acromegaly, dopamine agonists, somatostatin analogues, and growth hormone receptor antagonist have been used as a monotherapy or the combination, and the high remission rate can be achieved. Pasireotide having high affinity to type 5 somatostatin receptors will be available for the patients presenting resistance against type 2 receptor agonists, such as octreotide and lanreotide. The preceding treatment with somatostatin analogues is beneficial for improving the success rate of TSS. The chimera compounds of somatostatin analogues and dopamine agonists have been investigated. The medical treatments of Cushing's disease are challenging, if TSS is not successful. To suppress ACTH secretion, dopamine agonists and somatostatin analogues have been examined, but neither came to show a sufficient effect. Pasireotide reduces urinary cortisol excretion with a high remission rate. Adrenal enzyme inhibitors (AEIs), such as metyrapone, can inhibit cortisol synthesis form adrenal glands promptly and sufficiently in most of patients. LCI699, a newly developed AEI, is more potent than metyrapone and will be available. We should use available medical treatments for improving the prognosis and quality of life.